2017
DOI: 10.1590/1414-431x20165577
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and α-amylase: subclinical indicators of stress as cardiometabolic risk

Abstract: Currently, the potential for cardiovascular (CV) stress-induced risk is primarily based on the theoretical (obvious) side effects of stress on the CV system. Salivary cortisol and α-amylase, produced respectively by the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic-adrenomedullary (SAM) system during stress response, are still not included in the routine evaluation of CV risk and require additional and definitive validation. Therefore, this article overviews studies published between 2010 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 85 publications
1
54
0
7
Order By: Relevance
“…Increasing secretion of saliva from stimulation of the sympathetic nervous system by salivary glands is a response to stress (10,11). The present study showed that sAA was significantly increased in undesirable thermal comfort (PMV > +0.5).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Increasing secretion of saliva from stimulation of the sympathetic nervous system by salivary glands is a response to stress (10,11). The present study showed that sAA was significantly increased in undesirable thermal comfort (PMV > +0.5).…”
Section: Discussionmentioning
confidence: 46%
“…Signals are sent to the autonomic nervous system by the cerebral cortex in the presence of stress (9). Also, increase in saliva secretion and sAA occurs when preganglionic nerves of the sympathetic nervous system send signals to epithelial acinar cells in the salivary gland (10,11). Stress hormones, like cortisol and alpha-amylase, are released in the urine, blood, and saliva, with sAA being a non-invasive method for stress measurement among other methods (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of control over those variables diminishes the power of statistical analysis and relations may not be duly identified. 33,40 One of the greatest problems regarding saliva collection by the participants themselves is related to obtaining reliable samples, specially if they are obtained during the first hour upon awakening. During that time, cortisol levels vary extremely fast, so the adherence of participants to sample collection protocol becomes a determining factor for obtaining valid results.…”
mentioning
confidence: 99%
“…Необхідно відмітити, що об'єктом вивчення нейроендокринних змін в організмі при стресі були в основному тварини [4,9]. Особливості ендокрин-них реакцій на тривалий стрес, зокрема на хроніч-ну гіпоксію, у людини вивчені недостатньо.…”
unclassified
“…З цим пов'язано чима-ло можливих патологічних реакцій: симпато-адреналова активація зі схильністю до вазоконст-рикції, зниженню варіабельності серцевого ритму, гіперактивації та гіперагрегації тромбоцитів, підви-щенням частоти серцевих скорочень, артеріальної гіпертензії, підвищенням С-реактивного білку і про-запальних цитокінів -інтерлейкіну-1 та інтерлейкі-ну-6 [2,7]. Підвищений рівень кортизолу також сприяє розвитку та прогресуванню атеросклероти-чних процесів [9]. Через ці механізми стрес може провокувати серцево-судинні захворювання.…”
unclassified